INFLUENCE FACTORS INCOME OF JENGKOL FARMERS IN MANGGENG DISTRICT - Maisa Yahdi; Bagio; Zulkarnain (CV. Radja Publika, 2023)
The purpose of this research is to know the cost and income of jengkol farming in Manggeng District and to know the factors that influence it. The number of samples was 30 people who were jengkol farmers in Padang Village, Manggeng District. Results (t-test analysis at level α = 0.05%) the cost of pesticides and workers' wages are socio-economic variables that have a significant effect on the income level of jengkol farmers. The variables of education level (X1), farming experience (X2), amount of production (X3) and fertilizing costs (X4) did not have a significant effect on the level of income of jengkol farmers in Padang Village, Manggeng District. With the value of the coefficient of determination (R2) obtained, which is equal to 0.648, it means that 64.8% of the income of jengkol farmers is influenced by the variable level of education (X1), farming experience (X2), total production (X3) fertilizer costs (X4) pesticide costs (X5) and labor wages (X6). While 37.2% is influenced by variables outside the model in this study.